Bilingual Contexts Modulate the Inhibitory Control Network - Yang, Jing; Ye, Jianqiao; Wang, Ruiming; Zhou, Ke; Wu, Yan Jing (Frontiers in Psychology, 2018)
The present functional magnetic resonance imaging (fMRI) study investigated influences of language contexts on inhibitory control and the underlying neural processes. Thirty Cantonese-Mandarin-English trilingual speakers, who were highly proficient in Cantonese (L1) and Mandarin (L2), and moderately proficient in English (L3), performed a picture-naming task in three dual-language contexts (L1-L2, L2-L3, and L1-L3). After each of the three naming tasks, participants performed a flanker task, measuring contextual effects on the inhibitory control system. Behavioral results showed a typical flanker effect in the L2-L3 and L1-L3 condition, but not in the L1-L2 condition, which indicates contextual facilitation on inhibitory control performance by the L1-L2 context. Whole brain analysis of the fMRI data acquired during the flanker tasks showed more neural activations in the right prefrontal cortex and subcortical areas in the L2-L3 and L1-L3 condition on one hand as compared to the L1-L2 condition on the other hand, suggesting greater involvement of the cognitive control areas when participants were performing the flanker task in L2-L3 and L1-L3 contexts. Effective connectivity analyses displayed a cortical-subcortical-cerebellar circuitry for inhibitory control in the trilinguals. However, contrary to the right-lateralized network in the L1-L2 condition, functional networks for inhibitory control in the L2-L3 and L1-L3 condition are less integrated and more left-lateralized. These findings provide a novel perspective for investigating the interaction between bilingualism (multilingualism) and inhibitory control by demonstrating instant behavioral effects and neural plasticity as a function of changes in global language contexts.